2022
DOI: 10.3389/ffgc.2021.820800
|View full text |Cite
|
Sign up to set email alerts
|

Different Radial Growth Responses to Climate Change of Three Dominant Conifer Species in Temperate Forest, Northeastern China

Abstract: We conducted dendroclimatological study on three dominant conifer tree species, Pinus koraiensis, Larix olgensis, and Picea jezoensis, in northeastern China for a better understanding of climate change impacts on temperate forest growth, by discussing the radial growth relationships of these tree species and projecting their radial growth trends under the future climate change scenarios. Based on the tree-ring samples collected from the upper altitude of Changbai Mountain, ring width chronologies were built to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Under different climate scenarios in the future, the highly and moderately suitable areas of larch showed a downward trend, and with the increase in time and radiation intensity, the growth inhibition effect increased (Figure 9). Our finding supported the second hypothesis and was consistent with Wang et al (2022) that the radial growth of larch distributed in northeast China will show a decreasing trend with increasing periods (from 2020s to 2080s) and increasing emission scenarios (from RCP2.6 to RCP8.5). Another similar study showed that larch productivity was higher under low-concentration climate scenario (RCP 2.6), and lower under high-concentration climate scenarios (RCP6.0 and RCP8.5) in the future (Shen et al, 2015).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Under different climate scenarios in the future, the highly and moderately suitable areas of larch showed a downward trend, and with the increase in time and radiation intensity, the growth inhibition effect increased (Figure 9). Our finding supported the second hypothesis and was consistent with Wang et al (2022) that the radial growth of larch distributed in northeast China will show a decreasing trend with increasing periods (from 2020s to 2080s) and increasing emission scenarios (from RCP2.6 to RCP8.5). Another similar study showed that larch productivity was higher under low-concentration climate scenario (RCP 2.6), and lower under high-concentration climate scenarios (RCP6.0 and RCP8.5) in the future (Shen et al, 2015).…”
Section: Figuresupporting
confidence: 91%
“…In the high-altitude suitable distribution area of larch, the effect of temperature on the larch growth may be more important than that of rainfall. Additionally, larch growth rate would tend to decrease with increasing time and emission scenarios ( Wang et al., 2022 ). Therefore, we hypothesized that: (1) temperature has a greater effect on larch productivity than precipitation; and (2) larch productivity will be more inhibited by increasing years and radiation intensities.…”
Section: Introductionmentioning
confidence: 99%